UGONIN J FLAVONOID FROM TUNJUK LANGIT (Helminthostachys zeylanica Linn.) ROOT EXTRACT - Fitrya Fitrya; Lenny Anwar; Eliza Eliza; Muharni Muharni (Indonesian Journal of Chemistry, 2010)
A flavonoid compound was isolated from dried rihzomes of tunjuk langit (Helminthostachis zaylanica Lin), a traditional medicine from South Sumatera, Indonesia. Extraction was done by maceration methode and separation of isolated compound was conducted by chromatographic technique. The structure of this compound was determined base on spectroscopic data such as including UV, IR, 1-D, 2-D NMR, and comparison with the reported data. Based on spectral data analysis, concluded that isolated compound was Ugonin J (5,7,3',4'-tetrahydroxy-6-(6,6-dimethyil-2-methylenecyclo-hexylmethyl)flavone).